2011
DOI: 10.1007/s10620-011-1894-5
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Capsule Endoscopy Impacts Diagnosis and Management of Pediatric Inflammatory Bowel Disease: A Prospective Study

Abstract: In "suspected" pediatric IBD, CE often leads to a definitive diagnosis of CD. CE can lead to reclassification of IBD from UC/IC to CD and previously diagnosed CD patients may have a more significant burden of small bowel disease. These data may help integrate CE in evaluating IBD patients, lead to more targeted medical management changes and improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 23 publications
1
34
1
3
Order By: Relevance
“…Mohan et al (1) reported that 36 out of 42 patients (85.71%) had abnormal findings on OMOM capsule endoscopy in their study, among which 26 patients exhibited obscure gastrointestinal bleeding and a further 10 patients exhibited abdominal pain and/or diarrhea. However, the diagnostic yield in another study using the PillCam patency capsule was 77.78% (14/18) (19). In the present study, various types of lesion were detected in 54 out of 89 patients (60.67%), which was lower than the rates in previous studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Mohan et al (1) reported that 36 out of 42 patients (85.71%) had abnormal findings on OMOM capsule endoscopy in their study, among which 26 patients exhibited obscure gastrointestinal bleeding and a further 10 patients exhibited abdominal pain and/or diarrhea. However, the diagnostic yield in another study using the PillCam patency capsule was 77.78% (14/18) (19). In the present study, various types of lesion were detected in 54 out of 89 patients (60.67%), which was lower than the rates in previous studies.…”
Section: Discussioncontrasting
confidence: 86%
“…A large number of studies on small bowel lesions in CD using capsule endoscopy (CE) have clearly shown the superior diagnostic power of CE compared to other modalities [16, 17], as well as its usefulness in evaluation of disease activity [18, 19] and treatment selection [20, 21]. However, few studies have assessed UC small bowel lesions and none appear to have investigated the differences between these lesions in UC and CD.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment changes brought about by CE include onset of a new therapy, medication changes or withdrawal, and surgery indication (41,76,77). At a practical level this impact on CD management will depend on the reason why CE was indicated.…”
Section: Impact Of Capsule Endoscopy On Crohn's Diseasementioning
confidence: 99%
“…This impact is particularly relevant at pediatric ages since CE reclassifies as CD 50 % of ulcerative colitis and IC cases, detects proximal lesions unnoticed by other techniques in 50 % of subjects, and changes therapeutic decisions for 78 % of patients (76).…”
Section: Impact Of Capsule Endoscopy On Crohn's Diseasementioning
confidence: 99%